THE TRANSFORMATION OF ENGLISH AS A GLOBAL LANGUAGE IN THE WORLD - Pandarangga, Salmon (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2015)
Abstract: It is argued that English as a global language has some advantages to people around the world. One of the advantages is that English language is used as a tool of communication, empowerment and unification of people in the global community. In other words, English plays a very important role to unite all the people around the globe regardless their nationalities, cultural backgrounds, or races. However, for some scholars, English is seen as a potential threat to linguistic diversity in the world (Florey, 2010; Graddol, 1997; Tsuda, 2008; Phillipson, 2008). These scholars strongly believed that the dominant and powerful of English use in the global community has destroyed and killed most of the languages in the world. Some of the languages, as Florey claimed, become death languages. These scholars thus believed that English is responsible for the loss and death of thousands of minority native languages around the world. Instead of debating and taking side,Â it is argued that non-native speakers will use their own English teaching materials with their own context culturally , English will share the role as a global language with other languages e.g. Arabic, Spanish, Bahasa Indonesia, Mandarin, and there will be more new and various of English (es) forms around the world.Â Â Keywords: a global language, English, communication, linguistic diversity, transformation.